Strategies of Sustainable Development: External-economic, Law and Social Aspects - Saifullin A. I., Tarasova A. I., Vasilev A. V., Rudenko V. A., Sizykh D. S., Sizykh N. V., Ashrafzianov I. R., Iarulin I. F., Nikolaevna S. S., Iovleva O. O., Soldatova L. I., Dzokaeva Z. M., Lukhovskaia O. K., Beliaeva S. V., Kochetkova T. S., Plisov V. K., Kazibekova N. A., Butaev R. S., Kazibekov I. M., Kireeva M. M., Vostrova A. P., Fomina N. V. (Strategies of Sustainable Development: External-economic, Law and Social Aspects, 2022)
the research is based on the methodology of assessing the potential of the tourist complex of the region. The application of the methodology made it possible to conduct a qualitative expert assessment of the reproduction of the tourist resources of the region on the example of the Ivanovo region, a single destination. SWOT analysis was chosen as the main method, which made it possible to conduct a comprehensive strategic analysis of the industry and its external environment. The assessment of the potential of the tourist complex is aimed at identifying the most promising tourist destinations in the region and the formation of information resources in tourism.
Keywords: регион; рынок; комплекс; ресурсы; market; туристский потенциал; region; SWOT-анализ; SWOT-analysis; resources; факторный анализ; дестинация; информационные ресурсы в туриндустрии; tourism potential; complex; destination; factor analysis; information resources in the tourism industry